Tumor Immune Microenvironment Landscape in Glioma Identifies a Prognostic and Immunotherapeutic Signature - Zhang, Chunyu; Guo, Lirui; Su, Zhongzhou; Luo, Na; Tan, Yinqiu; Xu, Pengfei; Ye, Liguo; Tong, Shiao; Liu, Haitao; Li, Xiaobin; Chen, Qianxue; Tian, Daofeng (Frontiers in Cell and Developmental Biology, 2021)
The tumor immune microenvironment (TIME) has been recognized to be associated with sensitivity to immunotherapy and patient prognosis. Recent research demonstrates that assessing the TIME patterns on large-scale samples will expand insights into TIME, and providing guidance to formulate immunotherapy strategies for tumors. However, until now, thorough research has not yet been reported on the immune inﬁltration landscape of glioma. Herein, the CIBERSORT algorithm was used to unveil the TIME landscape of 1,975 glioma observations. Three TIME subtypes were established, and the TIMEscore was calculated by LASSO-COX analysis. The high TIMEscore was distinguished by an elevated tumor mutation burden (TMB) and activation of immune-related biological process, such as IL6-JAK-STAT3 signaling, and interferon gamma (IFN-γ) response, which may demonstrate the patients with high TIMEscore were more sensitive to immunotherapy. Multivariate analysis revealed that the TIMEscore could strongly and independently predict the prognosis of gliomas (CGGA cohort: HR: 2.134, P < 0.001; Gravendeel cohort: HR: 1.872, P < 0.001; Kamoun cohort: HR: 1.705, P < 0.001; TCGA cohort: HR: 2.033, P < 0.001; the combined cohort: HR: 1.626, P < 0.001), and survival advantage was evident among those who received chemotherapy. Finally, we validated the performance of the signature in human tissues from WHU (Wuhan University) dataset (HR: 15.090, P = 0.008). Our research suggested that the TIMEscore could be applied as an effective predictor for adjuvant therapy and prognosis assessment.